Sarcopenic obesity and severity of chronic venous disease in postmenopausal women - Kostromin, G. O.; Balaban, O. V.; Honza, R. V. (General Surgery, 2024)
Sarcopenic obesity (SO) is a functional and clinical condition that is characterised by the simultaneous existence of sarcopenia and excess adipose tissue. This condition may be one of the pathogenetic factors for chronic venous disease (CVD) of the lower extremities and chronic venous insufficiency (CVI), due to impaired muscle venous pump function. Furthermore, obesity is considered a risk factor for these conditions. Objective — to investigate the association of sarcopenia and sarcopenic obesity with the severity of chronic venous disease in postmenopausal women. Materials and methods. The study included 117 postmenopausal women who were divided into two groups: Group I — 87 (74.4%) women with CVD, and Group II—30 (25.6%) women without any signs of CVD. Within Group I, two subgroups were distinguished based on the class of CVD as defined by the CEAP classification system. Subgroup IA consisted of 45 women (51.7%) with CVD classes 1 and 2, which correspond to compensated chronic venous insufficiency (CVI). Subgroup IB included 42 women (48.3%) with CVD classes 3, 4, and 5, indicating subcompensated or decompensated CVI. The measurement of fat and lean mass was conducted using dual‑energy X‑ray absorptiometry with the Hologic device (Discovery WI, USA, 2015). The presence of sarcopenia was determined by the skeletal muscle assessment index ASM/height2, where ASM is the total appendicular skeletal muscle mass of the legs and arms. Sarcopenia was diagnosed when the value of ASM/height2 was <6.0 kg/m2. The diagnosis of SO was made in patients with sarcopenia and a body mass index >25 kg/m2. Results. The mean age of women was 67.32±9.12 years (46—86 years), the mean body mass index was 29.1±6.0 kg/m2 (18.4—50.1 kg/m2), and BMI/height2 was 6.72±0.864 kg/m2. Women in Group I had lower values of BMI/height2 (6.63±0.72 kg/m2) than women in Group II (6.97±1.0 kg/m2, p=0.056). Sarcopenia was detected in 27 (23.1%) women, and SO in 17 (14.5%). There was no statistically significant difference between the groups in the frequency of sarcopenia: in Group I, 5 (16.7%) women had sarcopenia, in Group II — 22 (25.3%), (p=0.334). The proportion of patients with SO in Group I was statistically significantly larger compared to Group II — 18.4 and 3.3% (p=0.044). There was an increase in the proportion of women with sarcopenia and SO with increasing severity of CVI: 8 (17.8%) patients in subgroup IA and 14 (33.3%) in subgroup IB had sarcopenia (p=0.095), and 4 (8.94%) and 12 (28.6%) had SO, respectively (p=0.018). Conclusions. Postmenopausal women with CVD were more likely to have SO (18.4%) compared to patients without CVD (3.3%, p=0.044). Postmenopausal women with subcompensated and decompensated CVI were more likely to have SO (12 (28.6%)) than women with compensated CVI (4 (8.94%, p=0.018, odds ratio 6.54, 95% confidence interval 0.83—51.58). Menopausal women with CVD were more likely to have sarcopenia and had a higher incidence of subcompensated and decompensated CVI compared to women without sarcopenia, but the difference was not statistically significant.